2016
DOI: 10.18632/oncotarget.9514
|View full text |Cite
|
Sign up to set email alerts
|

Tspan5 is an independent favourable prognostic factor and suppresses tumour growth in gastric cancer

Abstract: Tetraspanins are believed to interact with specific partner proteins forming tetraspanin-enriched microdomains and regulate some aspects of partner protein functions. However, the role of Tspan5 during pathological processes, particularly in cancer biology, remains unknown. Here we report that Tspan5 is significantly downregulated in gastric cancer (GC) and closely associated with clinicopathological features including tumour size and TNM stage. The expression of Tspan5 is inversely correlated with patient ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Interestingly, Tspan5 and Tspan15 differentially regulate the function of ADAM10 through a distinct membrane compartmentalization . The antagonistic effects between Tspan5 and Tspan15 have been also observed on cell proliferation since Tspan5 may inhibit the cell cycle whereas our study supports Tspan15 as activating the cell cycle. Recently, in vivo regulation of ADAM10 by Tspan15 has been shown .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Tspan5 and Tspan15 differentially regulate the function of ADAM10 through a distinct membrane compartmentalization . The antagonistic effects between Tspan5 and Tspan15 have been also observed on cell proliferation since Tspan5 may inhibit the cell cycle whereas our study supports Tspan15 as activating the cell cycle. Recently, in vivo regulation of ADAM10 by Tspan15 has been shown .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that TSPAN5 can regulate the function of ADAM10 on the cell surface and promote ADAM10‐mediated degradation of CD44 39 . Studies have also shown that TSPAN5 acts as a proapoptotic factor that inhibits tumor growth in gastric cancer 40 . On the other hand, TSPAN5 is positively regulated by the Notch signaling pathway 41 .…”
Section: Discussionmentioning
confidence: 99%
“…39 Studies have also shown that TSPAN5 acts as a proapoptotic factor that inhibits tumor growth in gastric cancer. 40 On the other hand, TSPAN5 is positively regulated by the Notch signaling pathway. 41 In this report, TSPAN5 was found to be poorly expressed in BCSCs, and overexpression of TSPAN5 abrogated miR-155-induced changes in stemness and DCA resistance in TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, accumulation evidence has suggested that potent GSIs were effective to inhibit γ-secretase activity in GC cell lines but were limited in their ability to induce apoptosis. 27 What about CCL? What about the combination of CCL and Notch pathway inhibitors?…”
Section: Discussionmentioning
confidence: 99%